Outcome following curative-intent electrochemotherapy for extramedullary plasmocytoma in dogs – case reports - Santos dos Anjos, Denner [UNESP]; Rossi, Ygor Amaral; Sierra, Oscar Rodrigo [UNESP]; Bueno, Cynthia Marchiori [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (Elsevier, 2020)
Plasma cell tumors can occur as solitary collections referred as extramedullary plasmocytoma (EMP). The present report describes four cases of EMP treated with a local nonthermal ablative approach. Four dogs were diagnosed with extramedullary plasmocytomas (EMP) in different body regions (oral cavity, digits, and lip). Since surgical excision was declined by the owners (maxillectomy; amputation or lip reconstruction), a curative-intent approach was indicated as solely treatment– electrochemotherapy (ECT). All the patients received ECT under general anesthesia using bleomycin intravenously (15,000 UI/m²) or cisplatin intratumorally (1mg/cm³). All dogs developed transitory ulceration and swelling one-week after procedure that completely healed within 30 days post-ECT. Complete remission was achieved in all cases and lasted for 515 (oral case), 695 (one digit), 90 (another digit case) and 240 (lip) days. These results suggested that ECT promoted remission in EMP cases being a possibility for local control in dogs affected by this disease.
Keywords: Bleomycin; Cisplatin; Electroporation; Plasma cells neoplasm